Chapter 2 Lessons of European VET? National systems and international prescriptions - Esmond, Bill (Taylor & Francis, 2022)
This chapter examines conflicting claims about the potential of European VET to provide a model for technical and vocational systems across the world. Technocratic accounts by international policy bodies, especially the OECD and EU, have focused on the possibilities for VET to facilitate transitions to employment by providing early experiences of learning at work, drawing on the integration of VET into production systems, as in the German system, seen as a barrier to neoliberal convergence because maintaining key progressive features into service sectors. Conversely, universalist welfare states held to underpin VET in Scandinavia have meanwhile given way to dualised social policies which, echoing the welfare state literature, can be seen either as 'layered' parallel provision or the direct erosion of comprehensive policies. During the early post-war period VET systems incorporated progressive educational elements which have come under attack, as signs of emerging dualisation have undermined the more progressive features of VET in Europe. Challenges from higher levels of VET, particularly in its most employer-responsive forms, can be seen as signs of this emerging dualisation.